Postmortem Examination of Emu Bird (Dromaius novaehollandiae) in Ragunan Zoo - Pardede, Friselsa; Rahardi, Nindya Anandaputri; Edwar, Syafri; Mohamad, Kusdiantoro (Jurnal Medik Veteriner, 2022)
Ragunan Zoo is one of the ex-situ conservation sites in DKI Jakarta to protect the wildlife outside their natural habitat. The emu (Dromaius novaehollandiae) is one of the TMR collection animals originating from Australia. An emu bird named Lebo, aged 19 years, and male sex was found sick on January 12, 2022. Based on physical examination, the emu bird showed clinical symptoms of anorexia, unwilling to eat, lethargic, refusing or difficult to move, unable to lift his head, and inflammation of the right eye. No further examination was performed to determine the diagnosis. Treatments were taken symptomatically, namely the fluid therapy, injection of vitamins and energy sources, antibiotics, and anti-inflammatory. The emu was found dead on February 6, 2022 and a necropsy was performed. Postmortem findings obtained were glossitis, ventriculitis, gizzard erosion, hemorrhagic enteritis, hepatic lipidosis, epicarditis, testicular atrophy, and orchitis. Diagnosis of suspected cause of death is damage and decreased function of various organs of the body.